Modelling Matambú bean (Phaseolus vulgaris) hydration kinetics using automated digital image analysis - Cubillo, Ovidio Valerio (2020)
Common bean is one of the most consumed crops worldwide, and of great importance for food security in Central America. The aim of this study was to determine the speed in which Matambú bean (Phaseolus vulgaris) expands after grain soaking. An automated digital image processing pipeline for measuring individual grain volume and simultaneously retaining its integrity was validated and used. Volumetric expansion was evaluated with Peleg and sigmoid models for water temperatures of 20-70 oC.The equations kinetic parameters weredescribed as functions of temperature using the Arrhenius equation with an activation energy of 22.410kJ mol-1. The obtained results are potentially useful for future studies on food properties, process and packaging design.